2020
DOI: 10.2169/internalmedicine.4998-20
|View full text |Cite
|
Sign up to set email alerts
|

Continued Aspirin Treatment May Be a Risk Factor of Delayed Bleeding after Gastric Endoscopic Submucosal Dissection under Heparin Replacement: A Retrospective Multicenter Study

Abstract: Objective Gastric endoscopic submucosal dissection (ESD) under heparin replacement (HR) of warfarin reportedly has a high risk of delayed bleeding (24-57%). It is possible that the delayed bleeding risk may have changed over the years. We evaluated the current risk of delayed bleeding after gastric ESD under HR of anticoagulant agents. Methods We retrospectively reviewed the delayed bleeding rate and analyzed the risk factors for delayed bleeding. Patients Consecutive patients who underwent gastric ESD under H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Detailed information about the excluded studies is presented in the supporting information. Eventually, 30 articles were included 24–53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information about the excluded studies is presented in the supporting information. Eventually, 30 articles were included 24–53 …”
Section: Resultsmentioning
confidence: 99%
“…Others were conducted in Japan. Ten studies focused on PPB of DOACs and warfarin in ESD 24,25,27,29,37,40,41,43,46,50 . Only two studies mentioned the usage of epinephrine as injection solution 50,53 .…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the full-text of the remaining 27 articles, a total of 19 studies were found to be ineligible for the inclusion criteria, and were excluded. Finally, eight studies 11 12 13 14 15 16 17 18 were included for the meta-analysis. Results of the study flow diagram are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of five articles 11 12 13 17 18 were included in the network. Based on the management of anticoagulants, six different groups assigned.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation